PENGARUH DIMENSI KUALITAS JASA TERHADAP KEPUASAN PELANGGAN PADA PDAM KOTA PADANG - Darmawanto, Ridno; Natassia, 2Rizky; Kemala Sari, 3Mareta (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This study was conducted to determine the effect of the dimensions of service quality on customer satisfaction PDAM Padang . The population in this study is a customer PDAM Padang is still active until 2013 the number of 75.094 while the total sample of 100 respondents was obtained from the calculation using the formula Slovin . The sampling technique was accidental sampling . Analysis method used is descriptive analysis , the classical assumption test and multiple linear regression analysis and hypothesis testing . Based on the results showed that the physical evidence , assurance and empathy do not have a positive and significant effect on customer satisfaction in PDAM Padang . It is evident that a significant level > 0.05 alpha . While reliability and responsiveness has a positive and significant effect on satisfaction pelaggan on PDAM Padang where significant levels < 0.05 alpha . Then simultaneously tangibles , reliability , responsiveness , assurance and empathy has a positive and significant effect on customer satisfaction with PDAM Padang calculated F value significant at 6.161 and 0.000 < 0.05 . From the research , it was found that the physical evidence , reliability , responsiveness , assurance and empathy only have the effect of 75.3 % to 24.7 % , while customer satisfaction is determined by other factors .